2012
DOI: 10.1111/ina.12003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cleaner-burning cookstove intervention on blood pressure in Nicaraguan women

Abstract: Few studies have evaluated the cardiovascular-related effects of indoor biomass burning or the role of characteristics such as age and obesity status, in this relationship. We examined the impact of a cleaner-burning cookstove intervention on blood pressure among Nicaraguan women using an open fire at baseline; we also evaluated heterogeneity of the impact by subgroups of the population. We evaluated changes in systolic and diastolic blood pressure from baseline to post-intervention (range: 273–383 days) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 51 publications
6
52
3
Order By: Relevance
“…Our results are consistent with several intervention studies in Latin America that found a decrease in SBP (∼3-6 mmHg) in older women who switched from a traditional open fire cookstove to a less-polluting chimney stove (40,41). Although blood pressure is an important risk factor for cardiovascular diseases and overall global burden of disease (1), further research should assess the associations of BC with other health outcomes, including those in vulnerable populations like children.…”
Section: Discussionsupporting
confidence: 88%
“…Our results are consistent with several intervention studies in Latin America that found a decrease in SBP (∼3-6 mmHg) in older women who switched from a traditional open fire cookstove to a less-polluting chimney stove (40,41). Although blood pressure is an important risk factor for cardiovascular diseases and overall global burden of disease (1), further research should assess the associations of BC with other health outcomes, including those in vulnerable populations like children.…”
Section: Discussionsupporting
confidence: 88%
“…These emissions degrade visibility and contribute to human morbidity and premature mortality (Sakamoto et al, 2016;Silva et al, 2013). Human exposure to biomass burning emissions has been associated with respiratory outcomes such as asthma, bronchitis, and COPD (Atkinson et al, 2015;Cohen et al, 2005;Gan et al, 2013) and cardiovascular outcomes such as high blood pressure, stroke, and arrhythmia (Brook et al, 2004;Clark et al, 2013;Pope et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Kalpana Balakrishnan provides an updated report on the situation focusing on India in this volume. More reports from Africa, Latin America [17,18] and Asia [19] have brought forward similar findings and led to a wide range of activities and changes, such as demonstrated in the pictures from a kitchen in San Carlos, Nicaragua (Figs. 2 and 3).…”
Section: Prefacementioning
confidence: 65%